An assessment of climate change induced improvisation strategies adopted by small scale farmers in Zhombe communal area. - Mabuto, Adeline (Midlands State University, 2018)
Climate change has negative implications on small scale farmers in Zhombe Communal area as evidenced by the failure of agricultural production and poor rural living standards. The farmers within the area have adopted different improvisation strategies as a way of adapting to the climatic changes. The strategies include plant staggering, stream bank cultivation, irrigation farming, organic farming, conservation farming, harnessing IKS, and growing of small grain drought resistant crops and short season varieties. However, even if such methods have been adopted, the community still suffers the negative implications by climate change. Therefore the main objective of the study focuses on assessing the effectiveness of these improvisation strategies by small scale farmers evaluating their ability in coping up with the climatic situations at hand. In accessing the needed information, the research employed qualitative approach where the community gave vivid description on the severity of climate change, the adaptation strategies and the effectiveness of these strategies. The researcher used purposive sampling on interviews and questionnaire as well as the specific study area she wanted to focus on. Improvisation strategies by farmers were successful in coping with climatic changes though they are some few which are not effectively dealing with its impacts as being as being analyzed by the research. The research recommends for various actors to be employed for effective adaptation programming to take place within the community.